2013
DOI: 10.1186/1746-1596-8-10
|View full text |Cite
|
Sign up to set email alerts
|

Associations of beta-catenin alterations and MSI screening status with expression of key cell cycle regulating proteins and survival from colorectal cancer

Abstract: BackgroundDespite their pivotal roles in colorectal carcinogenesis, the interrelationship and prognostic significance of beta-catenin alterations and microsatellite instability (MSI) in colorectal cancer (CRC) needs to be further clarified. In this paper, we studied the associations between beta-catenin overexpression and MSI status with survival from CRC, and with expression of p21, p27, cyclin D1 and p53, in a large, prospective cohort study.MethodsImmunohistochemical MSI-screening status and expression of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 45 publications
2
58
1
2
Order By: Relevance
“…However, the prognostic significance of β-catenin expression in CRC remains unclear. Previous studies as well as our study showed the worse survival outcome for patients with high expression of nuclear β-catenin [35, 36], whereas some showed that the high nuclear expression was associated with a better prognosis [37, 38], and other studies even failed to find any predictive value of nuclear β-catenin in CRC [39, 40]. Further studies are needed to verify the predictive value of β-catenin in CRC.…”
Section: Discussionmentioning
confidence: 43%
“…However, the prognostic significance of β-catenin expression in CRC remains unclear. Previous studies as well as our study showed the worse survival outcome for patients with high expression of nuclear β-catenin [35, 36], whereas some showed that the high nuclear expression was associated with a better prognosis [37, 38], and other studies even failed to find any predictive value of nuclear β-catenin in CRC [39, 40]. Further studies are needed to verify the predictive value of β-catenin in CRC.…”
Section: Discussionmentioning
confidence: 43%
“…A total of 6216 cases, based on 29 studies that revealed a relationship between nuclear β-catenin expression and pathological features or DFS/5-year OS, were investigated and their major clinical characteristics are summarized in Table 1. [14,15,1821,25–47] In addition, 9 studies showed a relationship between cytoplasmic β-catenin expression and pathological features or OS [17,1921,25,33,34,37,43] (Table 2). Thirteen studies were selected for analysis of the prognostic value of reduced β-catenin expression in the membrane of CRC [17,1921,26,31,34,35,38,43,48–50] (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…[1417] However, other studies did not present this association. [18,19] The variable and contradictory results were also observed regarding the correlation between the reduced membranous β-catenin expression and the prognosis in patients with CRC. [17,1921] A previous analysis suggested that β-catenin overexpression in nucleus, rather than in cytoplasm, was associated with poor prognosis of CRC.…”
Section: Introductionmentioning
confidence: 99%
“…While some studies have reported worse outcome for patients with low expression of β-catenin in the nucleus and other compartments (2730), others have reported no difference in prognosis (26, 31, 43), and yet others have found that strong expression is associated with poor outcome (22, 3234). The literature on E-cadherin is also marked by conflicting results, where some groups have reported no prognostic effect of altered E-cadherin expression (35, 36), whereas others have reported that patients with low E-cadherin expression have a poor prognosis (37, 38, 58).…”
Section: Discussionmentioning
confidence: 99%